(untitled) (Orinoquia, 2021)
Frequent or seasonal exposures to helminths that do not cause chronic infections are associated with an increase in allergic inflammation, a situation that could be extrapolated to human toxocariasis. The objective of this research was to determine the frequency of seropositives to Toxocara spp. among atopic students and the relationship between atopy and seropositivity to Toxocara spp. Within the materials and methods, a cross-sectional observational study was used where, for convenience, 90 students from the Nursing, Regency in Pharmacy and MVZ programs of the Universidad de los Llanos were selected, who according to the completion of the ISAAC phase III questionnaire are presumed to suffer from atopic disease. ; to develop in them the skin allergic hypersensitization test (PHAC), using extracts of Blomia tropicalis and Dermatophagoides pteronyssius. In students positive to this test, blood samples were taken for eosinophil count and in-house immunoassay for IgG anti-Toxocara spp. As a result, of the 90 students with a history of atopic disease, only 33.3% were positive for one or both dust mites in the PHAC and their blood eosinophil count was normal 66.6%, mean 26.7 % and moderate 6.7%. The frequency of seropositivity to Toxocara spp. was 73.3% (OD 1.009 cut-off). The OR between atopy and seropositivity to Toxocara spp. was 1.18 (95% CI 0.24-5.7). Colombia is one of the countries with a high endemicity of toxocariasis with prevalences between 40.4-54.4%, data confirmed according to the frequency of seropositives to Toxocara spp. found in atopic people under study. No relationship was found between atopy and seropositivity to Toxocara spp.